2014
DOI: 10.7314/apjcp.2014.15.7.3163
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Choice of Surgery in Asian Patients with Early Breast Cancer in A Middle Income Country

Abstract: Background: Breast-conserving surgery (BCS) plus radiotherapy is equivalent to modified radical mastectomy (MRM) in terms of outcome. However there is wide variation in mastectomy rates dependent both on tumour and patient characteristics. Objective: This study aimed to assess the determinants of surgery choice in Asian patients with early breast cancer in a middle-income country. Materials and Methods: 184 patients with early breast cancer treated between Jan 2008 and Dec 2010 were recruited to complete a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(78 citation statements)
references
References 18 publications
4
74
0
Order By: Relevance
“…This fear of cancer recurrence as a deciding factor for choosing mastectomy is similar to the findings of previous studies from western countries , , as well as in Hong Kong. Interestingly, a study performed in Malaysia found no significant difference in terms of fear of cancer recurrence between women who chose mastectomy and those who chose BCT.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This fear of cancer recurrence as a deciding factor for choosing mastectomy is similar to the findings of previous studies from western countries , , as well as in Hong Kong. Interestingly, a study performed in Malaysia found no significant difference in terms of fear of cancer recurrence between women who chose mastectomy and those who chose BCT.…”
Section: Discussionsupporting
confidence: 88%
“…The respondents in this study were largely aged over 50 years, of Chinese ethnicity, and of secondary school level of education and below. The demographic profile of the recruited patients was similar to that of patients who chose to undergo mastectomy in other studies.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…79 Common demographic factors examined in such studies include age, education, and ethnicity. Age has shown many discrepant results, with the most consistent finding being an increased likelihood of undergoing mastectomy in younger age groups under 40 or 50.…”
Section: Introductionmentioning
confidence: 99%